2006
DOI: 10.1002/adma.200601177
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Charge‐Carrier Pathways for Organic Electronics

Abstract: Controlling self‐organization: The chemical variation of alkyl substituents on the discotic hexa‐peri‐hexabenzocoronene allows the molecular orientation to be controlled with respect to a substrate, which is a key prerequisite to implement such semiconductors into electronic devices (see figure). Charge‐carrier mobility determined by a time‐of‐flight technique reveals a high anisotropy along and perpendicular to the established columnar superstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 28 publications
0
68
0
1
Order By: Relevance
“…The time-of-flight (TOF) results revealed that the quality of the organization (columnar assemblies) and the molecular orientation (''face on'' and ''edge on'') is crucial for the charge-carrier mobility. [88] This proves that supramolecular organization is electronically relevant and emphasizes that PAHs are promising candidates for implementation in organic electronics. Nevertheless, the choice of the processing techniques is a key-step in the utilization of organic molecules in devices.…”
Section: Variation Of the Corementioning
confidence: 90%
“…The time-of-flight (TOF) results revealed that the quality of the organization (columnar assemblies) and the molecular orientation (''face on'' and ''edge on'') is crucial for the charge-carrier mobility. [88] This proves that supramolecular organization is electronically relevant and emphasizes that PAHs are promising candidates for implementation in organic electronics. Nevertheless, the choice of the processing techniques is a key-step in the utilization of organic molecules in devices.…”
Section: Variation Of the Corementioning
confidence: 90%
“…Typically, a dispersive transport is obtained for low-ordered films, while a non-dispersive photocurrent is determined for perfectly aligned structures indicating reduced charge trapping. [53] It has to be emphasized that a homeotropic phase on only one surface was reported in only a few cases, which opens the possibility of practical application in photovoltaics.…”
Section: à4mentioning
confidence: 99%
“…[48] Da diese üblicherweise keine intrinsischen Ladungen enthalten, wurden Ladungen durch Dotieren oder durch Photoprozesse erzeugt. Vaughan und Mitarbeiter [49] [54] in der aber eine Domänenbildung auftritt, die wiederum zu Ladungsfallen an den Domänen- [56] Mit einem quantenchemischen Ansatz wurden die für hohe Ladungsträgerbeweglichkeit erforderlichen Molekül-merkmale in Triphenylen, Hexaazatriphenylen, Hexaazatrinaphthylen und Hexa-peri-hexabenzocoronen (Schema 1 und 37) auf der Grundlage berechneter Struktur-EigenschaftsBeziehungen [57] …”
Section: Elektrische Leitfähigkeitunclassified